2012
DOI: 10.1515/cclm-2012-0330
|View full text |Cite
|
Sign up to set email alerts
|

Distributions and ranges of values of blood and urinary biomarker of inflammation and oxidative stress in the workers engaged in office machine manufactures: evaluation of reference values

Abstract: This is the first report assessing the distributions and reference values of inflammatory biomarker levels in a large scaled cohort. We observed age related changes of some of the biomarkers. We could not detect any differences of the studied biomarker values between the toner exposed and the control workers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
1

Year Published

2016
2016
2025
2025

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 22 publications
1
2
0
1
Order By: Relevance
“…As the toner-handling group did not show consistently higher values than the reference group in any biomarker throughout the study period, there seem to have been no health effects related to toner exposure. Previous studies similarly reported no effect of toner exposure on biomarker levels, which was consistent with our results [9,10].…”
Section: Biomarker Analysessupporting
confidence: 93%
See 1 more Smart Citation
“…As the toner-handling group did not show consistently higher values than the reference group in any biomarker throughout the study period, there seem to have been no health effects related to toner exposure. Previous studies similarly reported no effect of toner exposure on biomarker levels, which was consistent with our results [9,10].…”
Section: Biomarker Analysessupporting
confidence: 93%
“…Therefore, an epidemiological study among humans with known exposure status is required to clarify the effects of toner exposure on health. Some studies have investigated toner exposure and its effects on health in Japanese toner and photocopier manufacturing companies using various methods and have reported no health effects of toner exposure [9][10][11][12][13][14]. However, some of these studies have had a cross-sectional study design whereas others have had other limitations such as a very small sample size.…”
Section: Introductionmentioning
confidence: 99%
“…The influence of the toner particles on seven biomarkers (serum C-reactive protein (CRP), IgE, interleukin (IL-4, IL-6, and IL-8), serum interferon- γ (IFN- γ ), and urine 8-hydroxy-2′-deoxyguanosine (8OHdG)) was investigated by Murase et al [109]. They conducted a prospective cohort study (toner exposed and unexposed) with a five-year follow-up and measured annually the biomarkers.…”
Section: Diagnostic Tests and Statistical Methodsmentioning
confidence: 99%
“…Η προφλεγµονώδης κυτταροκίνη IL-8, βρίσκεται στα αναµενόµενα πλαίσια για ασθενείς σε κίνδυνο για ανάπτυξη ARDS, σύµφωνα µε την µελέτη της Kurdowska et al, 2001 (58) . Για την CRP οι φυσιολογκές τιµές είναι < 0,8 mg/dl, µε τον µέσο όρο της µελέτης να βρίσκεται άνωθεν των τιµών αυτών, ενώ η προφλεγµονώδης κυτταροκίνη IL-6, µπορεί να θεωρηθεί σε φυσιολογικά πλαίσια για όριο τιµών 0,4-4,9 pg/mL, µε τις τιµές την παρούσα µελέτη να είναι ιδιαίτερα αυξηµένες (217) . (218) .…”
Section: μετρήσεις κυτταροκινών στο αίµαunclassified